Fotografer dan Dinamika Jurnalisme Positif perspektif Jurnalistik Islam: Studi Media Online Times Indonesia - Muhammad Iqbal; M. Badar (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2022)
Photography has an important role in the world of journalism. However, someone who works as a photographer doesn't just take pictures based on his imagination based on the photographer's own volition. This study aims to describe the role of photography and the dynamics of positive journalism in online media at www.timesindonesia.com. This research uses qualitative research with descriptive analysis, which describes phenomena and facts systematically and analytically. Is the role of photographers and the dynamics of positive journalism from the perspective of Islamic Journalism by having a case study in the online media Times Indonesia. The data collection method was based on the virtual ethnographic paradigm in cyber media (Nasrullah, 2014), especially online documentation from the work of photographer Senda Hardika Prasasti for the 2016-2017 period, while the results of the interviews were conducted on July 10, 2017. The analysis of this data used analytical techniques. The Miles and Huberman model; is in the form of data reduction analysis, data display, and conclusion verification. The results of the study indicate that the role of photographers in Timesindonesia has fulfilled the rules of positive and constructive photojournalism, including; (1) Appropriate/appropriate photo composition; (2) Contains journalistic elements (5W+1H); (3) Does not destroy the reality of events; and (4) Has more value than ordinary photos. The recommendations for all photographers in this study, among others; are (a) A photographer should always comply with the applicable journalistic photography ethics and journalistic photography publication ethics, and (b) Do not be easily bribed with material to produce and publish fake photos that can cause polemics in the community. The research also states that Islamic Journalism is a constructive solution to developing online mass media based on religious and humanitarian knowledge (humanism).